Editorial - International Journal of Sustainable Energy Planning and Management Vol 11 - Poul Alberg Østergaard; Neven Duic (International Journal of Sustainable Energy Planning and Management, 2016)
This editorial introduces the 11th volume of the International Journal of Sustainable Energy Planning and Management. The volume addresses smart energy systems and the optimal ways of integrating renewable energy into these. Two of the contributions are from the perspective of energy storage with one arguing that other storage options are preferable to designated electricity storage. This includes thermal storages for house heating and gas and liquid fuel storage for e.g. the transportation sector.  Secondly, a paper investigates more narrowly communal vs individual electricity storage in residential PV systems with a view to lowering grid dependency. Lastly, an analysis investigates the role of flexible electricity demand as a means to integrate fluctuating renewable energy sources such as wind and PV.